PERANCANGAN APLIKASI SISTEM INFORMASI PARIWISATA BERBASIS WEB UNTUK DESA GIRITENGAH, BOROBUDUR - Sherly Sherly; Desi Arisandi; Tony Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Giritengah village is a village located in the district of Borobudur, Magelang, Central Java Province is approximately 5 km to the southwest of Borobudur. Giritengah village has a variety of beautiful attractions. But the village is not known a lot of tourists because of the lack of information about tourist attractions and insufficient promotion method resulted Giritengah village is less known by tourists. Designing information system, Giritengah Village tourism is expected to introduce and provide information about the Village Giritengah and can help travelers to get information about tourist attractions and tourist services contained in the village Giritengah. The application development is also expected to increase tourist visits to the village of Giritengah. Methodology used to design this application is SDLC (System Development Life Cycle). Software support used in the design of this system is PHP, HTML, and Mysql contained in PhpMyAdmin, and uses Google Maps to display the location map travel by the coordinates of each attraction or tour